Physicochemical and Fatty Acids Composition of Barberry Integerrima Seed - Tavakoli Atefe; Ali Sahari Mohammad; Barzegar Mohsen; Asghari Ghajari Mohsen (International Journal of Nutrition, 2016)
In this study, chemical composition of Barberry integerrima seed and physicochemical properties and fatty acids composition of its oil were determined. The seeds contained 11.4 % oil and protein, moisture, crude fiber and ash contents were 17.0%, 19.1%, 48.8% and 2.9%, respectively. The main fatty acids recognized by gas chromatography were linolenic (ω-3), linoleic (ω-6) and oleic (ω-9) acid (38.3, 37.0, 15.5%, respectively). The density and refractive index of the extracted barberry seed oil were 0.821 and 1.4780, respectively. FFA (% as oleic acid), acid value (mg KOH/g oil), iodine value (g I2/100 g oil), saponification number (mg KOH/ g oil), and unsaponifiable matter content (%) of the extracted oil from Barberry integerrima seeds were 0.70, 1.4, 180.0, 197.2, and 2.3, respectively. Color of extracted crude oil exhibited red unit 4.9, yellow unit 18.6 and blue unit 1.9, respectively. Total phenolics compounds (mg Gallic acid/kg oil), total tocopherols (mg/kg oil) and total sterols (mg/100g oil), were 323.0, 111.1 and 762.3, respectively. Specific extinctions at 232 nm (K232) and 270 nm (K270) and R-value (K232/K270) were 3.9, 2.2 and 1.8, respectively. The present study revealed that Barberry integerrima seed oil can be a valuable source of oil for food, pharmaceutics and cosmetics uses.
Keywords: Physicochemical